Fatty Acids From Biosynthesis to Human Health - Froyen, Erik (Biochemistry, 2023)
Fatty Acids - From Biosynthesis to Human Health discusses how fatty acids are associated with various diseases and health conditions, such as cardiovascular disease, cancer, inflammation, autoimmune diseases, and metabolic disorders. Nutrition, fatty acid, and therapeutic recommendations are provided for individuals with certain diseases and health conditions and for those interested in decreasing the risk factors for chronic diseases. This book also covers biosynthesis and processing of fatty acids, which address human health and environmental concerns.